Disparities in patients’ perceptions on access to healthcare: implications to promote health equity in Palestine - Ola Al Eker; Asma Imam (Global Public Health)
Equitable access to healthcare is essential for achieving Universal Health Coverage (UHC) and improving health outcomes. This cross-sectional study examines patients’ perceived access to healthcare services in the West Bank, providing insights into patients’ perceptions of health disparities. Data were collected using stratified convenient sampling of 486 chronic patients at governmental primary healthcare centers in three governorates. A 5-points Likert scale questionnaire was used, based on the ‘6A’ dimensions for healthcare access: affordability, acceptability, accommodation, accessibility, availability, and awareness. The overall healthcare access mean score was 3.29 (SD = 0.46), with only 38.5% of participants reporting satisfactory access levels. Only acceptability (mean =3.75, SD = 0.55), and awareness (mean = 3.66, SD = 0.61) dimensions demonstrated significantly positive perceptions. Bivariate analysis identified income as the main significant determinant for access disparities (Kruskal–Wallis Test χ²= 75.9, p < 0.001). Place of residency, education and income significantly contributed to the disparities within the different access dimensions. The findings highlight significant challenges in healthcare access in the West Bank, particularly regarding services availability and financial affordability. These barriers extremely affect vulnerable populations, exacerbating existing health inequities and undermining efforts toward UHC. The findings emphasise the urgent need for policy interventions to address financial protection, expand service availability, and strengthen healthcare provision.